Prevalence of Intestinal Parasites in Houses Mice (Musmusculus ) among Different Localities of Erbil City, Kurdistan Iraq - Saida, Louis A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Parasites of small mammal’s (houses mice) living in human areas cause a tremendous burden of vector borne disease. Small mammals infected with parasites can readily facilitate parasitic transmission to humans and other susceptible animal hosts. The objective of our study is to determine the presence of intestinal parasites in mice collected from five different popular localities in Erbil city during the period of (2014-2015). Out of total (60) mice (Musmusculus) examined, 34(56.6%) of which were infected with (1-3) species of intestinal parasites. In this study eight species of intestinal parasites were detected and identified as follow as: Four types of intestinal protozoans: Entamoebamuris 6(17.6%), Trichomonasmuris 3(8.8%), Giardia muris 4(11.7%) and Emeria sp.2(5.8%),two types of Cestodes: Hymenolepis nana8(23.5%) and Hymenolepisdiminuta 3(8.8%), and twotypesof mice pinworm: Aspiculuristetraptera4 (11.7%) and Syphaciaobvelata 4 (11.7%). Among total mice (34) infected with intestinal parasites, infection with helminthes were more prevalence 19(55.8%) than protozoans15(44.1%). According to the multiple infectionwith the parasites, we found that mice infected with the single infections 20(58.8%) were higher than both double 10(29.4%), and triple 4(11.7), and about sex of mice involvement, we found that females were highly infected 21(61.7%) than males13 (38.2%). The results of the present study showedthat the prevalence of the parasites in mice collected from Hayaskary were highlyinfected (29.4%) compared with the other localities of the study areas.
Keywords: Houses mice; intestinal parasites; ErbilKurdistan; Iraq